1989
DOI: 10.3758/bf03208028
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of discrimination and identification of vibrotactile patterns

Abstract: Both discrimination and identification tasks have been used to assess subjects' abilities to perceive vibratory spatial patterns presented to the skin. The present study examined discrimination and identification performance under comparable conditions. In Experiment 1, subjects attempted to discriminate a pair of patterns on some blocks of trials and to identify both members of a pair on other blocks. For both tasks, the time between the members of the pair was varied. Discrimination performance could be pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…A two-way repeated measures analysis of variance (ANOVA) on the P(C) max data revealed an effect oflocation [ILs vs [F(6,30) = O.54,p > .05). The effect of SOA reflects the general improvement in performance as the time between patterns was increased, a result that has been found in previous studies of discrimination, and that may be due to reduced temporal masking (Cholewiak & Craig, 1984;Craig, 1983a;Homer, 1991;Horner & Craig, 1989). The …”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…A two-way repeated measures analysis of variance (ANOVA) on the P(C) max data revealed an effect oflocation [ILs vs [F(6,30) = O.54,p > .05). The effect of SOA reflects the general improvement in performance as the time between patterns was increased, a result that has been found in previous studies of discrimination, and that may be due to reduced temporal masking (Cholewiak & Craig, 1984;Craig, 1983a;Homer, 1991;Horner & Craig, 1989). The …”
Section: Methodsmentioning
confidence: 61%
“…Previous studies ofvibrotacti1e-pattern discrimination have varied the time between pattern onsets-the stimulus onset asynchrony (SOA)-in order to examine temporal characteristics ofpattern processing (Cholewiak & Craig, 1984;Craig, 1983aCraig, , 1985aHorner, 1991Horner, , 1992Horner & Craig, 1989). In Experiment I, it was varied for several reasons: (1) the subjects would feel only a single stimulus if patterns simultaneously occupied ILs; (2) spatial patterns are usually felt sequentially as the fingerpad moves across a surface, and hence the time between successive patterns varies; and (3) varying the SOA manipulated the rate at which information was presented to the skin, thereby determining the extent to which varying location affected the rate at which information was processed.…”
Section: Methodsmentioning
confidence: 99%
“…Only the main effects and interactions reaching at least the .05 level of significance are discussed here. There was a main effect of masker shape, showing that accuracy was lower in the presence ofDS than ofSS maskers [F(l,4) Many studies have shown that performance improves with increasing SOA when DS maskers are at SLoc (Cholewiak & Craig, 1984;Craig, 1976Craig, , 1978Craig, , 1982Craig, , 1983Craig, , 1985aCraig & Evans, 1987;Evans, 1987;Evans & Craig, 1986;Horner, 1991;Horner & Craig, 1989). Such improvement may be due to several factors, including a decline in temporal integration of target and masker features at longer SOAs (Evans, 1987;Evans & Craig, 1986) which would improve the clarity of individual features within the target.…”
Section: Resultsmentioning
confidence: 99%
“…asynchrony (SOA)-in order to examine the temporal The vibratory array measures 11.45 mm wide x 27.14 mm high characteristics of pattern processing (Cholewiak & and consists of 144 blunt pins arranged in 24 rows (1.18 mm sep- Craig, 1984;Craig, 1976Craig, , 1980Craig, , 1982Craig, , 1983Craig, , 1985a; Craig arating rows) and six columns (2.29 mm separating columns). & Evans, 1987;Evans, 1987;Evans & Craig, 1986; Each ofthe .25-mm-diameter pins vibrated at 230 Hz and at a comfortable intensity well above threshold, 33 V to the driver circuits, Horner, 1991;Horner & Craig, 1989). SOA was varied resulting in a maximum skin indentation of65 microns (Bliss et aI., in Experiment 1 to determine the extent to which the 10-1970;Bliss & Linvill, 1966).…”
Section: )mentioning
confidence: 99%
“…They found differences between sites in the absolute levels of performance for both tasks, but in opposite directions. Specifically, observers were able to learn to identify the patterns far better when the patterns were presented to the finger than to the thigh, yet discrimination performance was superior on the thigh, illustrating a dissociation between the two tasks (see also Horner, 1991;Horner & Craig, 1989). The discrimination data, however, did suggest that there is a functional similarity in processing across sites (i.e., the shape of the curve describing the relationship of performance to stimulus onset asynchrony was the same for both sites).…”
mentioning
confidence: 99%